Dampak Kondisi Lingkungan Pesisir Terhadap Sosial Ekonomi Penduduk Kenjeran Surabaya - Shafa Jihan Anjani; Anggraeny Puspaningtyas (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Coastal environmental conditions have an impact on the economy of residents around the coast. It is hoped that environmental conditions that border directly with sea waters and the Madura Strait will have an impact on the economy of local communities who utilize natural resources. The risk of uncertain environmental conditions causes the Kenjeran coastal community to experience various impacts, both good and bad. The government should also play a role as a facilitator in the situation of communities experiencing difficulties. Therefore, this research analyzes how the impact of the coastal environment on Kenjeran Beach can affect the economy of coastal communities. This research uses a qualitative approach with descriptive research type. The results of the research show that there is an impact of coastal environmental conditions on the economy of the coastal community of Kenjeran Beach.